Cost of rotavirus diarrhea for programmatic evaluation of vaccination in Vietnam - Arthorn Riewpaiboon; Sunheang Shin; Thi Phuong Mai Le; Dinh Thiem Vu; Thi Hien Anh Nguyen; Neal Alexander; Duc Anh Dang; the Rotavirus Economic Study Group (BMC, 2016)
Abstract Background Rotavirus is the most common etiology of diarrhea-associated hospitalizations and clinic visits in Vietnamese children < 5 years old. To estimate the economic burden of rotavirus-associated formal healthcare encounters, an economic study was conducted. Methods A cost-of-illness study was performed from a societal perspective. Data were collected from children below the age of five years who presented to a clinic or hospital with symptoms of acute gastroenteritis (AGE). Patient-specific information on resource use and cost was obtained through caregiver interviews and medical chart review. Costs are presented in 2014 US dollar ($). Results A total of 557 children with symptoms of AGE were enrolled from March through June 2009, with mean age of 16.5 months. Of the 340 outpatients and 217 admitted patients enrolled, 41 % tested rotavirus positive. It was found that, from a societal perspective, the mean total cost of AGE was $175. Costs of patients with and without rotavirus were $217 and $158, respectively. From multiple regression analysis, it was found that rotavirus infection, patient age and receiving oral rehydration solution before visiting health facility had significant effect on the costs. Conclusions This study clearly demonstrated substantial economic burden of AGE including rotavirus disease. They were significantly greater than the previously reported cost estimates in Vietnam. These updated costs of illness result in more favorable vaccine cost-effectiveness than in previous economic evaluations.